Diagnosis of Fungi Associated with Wounds from Lying Patients at Al-Hussein Teaching Hospital in Dhi Qar Governorate - Iman Hadi Alfayyadh; Kadhim Mohan Manhil (Institute of Medico-legal Publications Pvt Ltd, 2022)
About 30 samples were collected from burn areas from patients attending Al-Hussein TeachingHospital in Dhi Qar governorate for the period between 2-4 for the year 2020. 7 types of fungi andyeasts, represented by the following fungi, have been isolated candida kruzei, candida tropicalis, andRhizopus, candida albican, candida glabrata, Aspirgillus spp, rhodotorella. The results showed thatAspergillus spp. Was dominant over the rest of the fungi, with a rate of 36.36% over the rest of the fungispecies, while candida albican yeast appeared with a frequency of 28.18% compared to the rest of theother fungi, and the rate of appearance of other fungi was about 12-3% compared to the rest of the otherfungi. The fungi were distinguished by the fact that they are all of the opportunistic type, which beginsto infect the body when there is a weakening of immunity or infection with the associated burns andulcers.